Tinjaun Yuridis Terhadap Permohonan Dispensasi Nikah Anak Dibawah Umur: (Studi Penetapan Pengadilan Agama Kraksaan Perkara Nomor 0092/PDT.P/2021/PA-KRS) - HA. Djazim Ma'shum; Pangestu Meyta TW (STIH Zainul Hasan Kraksaan Kraksaan, 2021)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the one and only God based on law number 1 of 1974 concerning marriage. This research is a literature study with the title